Nas sendas da criação literária de Moreira Campos: edição genética e estudo crítico-filológico de contos inéditos do autor - Lima, Elisabete Sampaio Alencar (2016)
The personal archive of Ceará writer José Maria Moreira Campos, officially donated by the family to the Federal University of Ceará, in 2007, is deposited in the Social Sciences Center Library of that University and composes the Acquis Writer Cearense. All these documents allows, in addition to the writer's memory consolidation, the development of studies and issues within the Philology and Genetic Criticism. The discovery of unpublished short stories of writer sparked our interest in studying them critically, from a philological reading, and present them through a genetic issue. To meet this goal, we review the concept of file and memory in order to understand how the information found in the personal file of the writer may help us better understand your biography, the reception of his work and his creative process. Thus, the biography of the writer is seen through interviews published in newspapers and books and documents found in his personal file. Here is the genetic vertical edition six unpublished short stories, namely: Os caminhos, A nova empregada, O elevador de carga, A mágoa, A mecha de cabelo and O suposto filho, constituted by the description, linearized transcript of the evidence and consideration of erasures the testimonies. Our goal with this thesis is to present, through editing and critical-philological study of erasures and genetic moments of unpublished author's short stories, the creative process Moreira Campos under the gaze of Philology and Genetic Criticism, and show how narratives were built and which elements were taken from the stories to become more concise.